Anti-Urease Activity of Essential oil and Phenolic compounds of Thymus vulgaris, Melaleuca alternifolia and Betula pendula against Proteus mirabilis isolates - Mohammed R. Mohammed1 , Ayyad W. Al – Shahwany1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was carried out to evaluate the activity essential oil and phenolic compounds ofThymus vulgaris, Melaleuca alternifolia and Betula pendula extracts against urinary tract infections causedby urease-producing from seven strains of bacteria Proteus mirabilis isolated from urinary tract infection.Microdilution technique has been used to evaluate antibacterial operations in sterile 96-well microtiter plates.Activity of urease and inhibition of urease assessed by indophenol test method. The results showed that M.alternifolia extract was the best antibacterial activities against all strains at 1.25 - 25 mg/ml. Also, 0.31 mg/ml of phenolic compounds and essential oil of M. alternifolia extract serves as effective dual acting 100%urease inhibitor to prevent and eliminate urease. Besides, the results of phytochemical detection show thatCoumarins, Terpenes, Alkaloids, Tannins, Flavonoids and Sesquiterpenes were present in M. alternifoliaextract, which may be have anti-urease possessing activity. Furthermore, these plants could be act as asource of antimicrobial compounds against P. mirabilis which are commonly impaired by the developmentof bladder and kidney stones.